Introduction To Intellectual Property (Ki) For High School Al Hanif In Cilegon - Inge Dwisvimiar; Sulasno Sulasno (KAIBON ABHINAYA : JURNAL PENGABDIAN MASYARAKAT, 2022)
Intellectual property is the result of human thought that is realized in the form of real works, and is not just an idea, idea, concept but the most important thing is its realization. Some people have ideas but are not necessarily able to realize these ideas in a tangible form. In connection with the above, the younger generation, including high school students, generally have many ideas, but not all of them have been realized. Therefore, this community service aims to provide an introduction and understanding related to intellectual property, to beginners, namely students from the Islamic Integrated High School (SMA IT) Putri AL Hanif in Cilegon City. The introduction and understanding of Intellectual Property need to be introduced to the students of SMA IT Putri Al Hanif from an early age by implementing Intellectual Property completely and correctly, there is a great opportunity for students and students to produce quality and highly competitive works. With this service activity, the school's awareness of the importance of Intellectual Property arises and fosters motivation to be creative and innovate. In general, Intellectual Property has not been exploited to its full potential, both in higher education and in secondary schools. The results of this community service can provide understanding to students, especially SMA IT Putri Al Hanif Cilegon City regarding Intellectual Property material which includes Communal Intellectual Property (Traditional Knowledge, Traditional Cultural Expressions, and Geographical Indications), Personal Intellectual Property (owned by industry). In the provision of service material, it is divided into 3 different classes, namely Language Class, Science and Social Sciences. They are very enthusiastic in listening, understanding, and discussing the introduction of intellectual property (IP). Therefore, there is a follow-up from the school to improve the work of its students so that the work is given legal protection through the intellectual property registration application process.